Prevalence of congenital defects in Swedish Hampshire, Landrace and Yorkshire pig breeds and opinions on their prevalence in Swedish commercial herds - Mattsson, Petra (2011)
This study concerns congenital defects in pigs; umbilical and scrotal hernia, cryptorchidism, kyphosis, splay legs, anal atresia, intersexuality and congenital tremor. The aim was to describe and estimate the prevalence of these defects and estimate the heritability for the most frequent defects, scrotal hernia and cryptorchidism in purebred Swedish Hampshire, Landrace and Yorkshire populations. Furthermore, information and opinions from herdsmen in commercial herds was collected and analysed. A low proportion of congenital defect pigs is of importance both from animal welfare and economic point of view. The accuracy of registration of the presence of defects in the litters has a decisive role for the ability to select against these defects. Linked with that is also the question to what degree these defects have a hereditary background.